2022
DOI: 10.1002/jmor.21468
|View full text |Cite
|
Sign up to set email alerts
|

Iliocapsularis: An exploration of the muscle and its omission in education

Abstract: Anterior hip joint musculature is classically characterized to include iliacus, psoas major, rectus femoris, and sartorius muscles. A lesser‐known muscle, iliocapsularis muscle (ICm), has made infrequent appearances in the literature for the last ~70 years, but potentially has important functional and clinical value. The purpose of this study is to review the historical prevalence of the ICm in peer‐reviewed literature (PRL), further explore the prevalence of the muscle in current anatomical textbooks (ATBs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, in the current study, aging was found to be negatively correlated only with the hip joint capsule, and not with the IC. Although it has not yet been confirmed in vivo, the IC is presumed to have a role in preventing impingement of the capsular ligament at the anterior hip joint (Breckling et al, 2022). The shear modulus of the IC did not change with age, and this could be because of the function to prevent hip impingement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the current study, aging was found to be negatively correlated only with the hip joint capsule, and not with the IC. Although it has not yet been confirmed in vivo, the IC is presumed to have a role in preventing impingement of the capsular ligament at the anterior hip joint (Breckling et al, 2022). The shear modulus of the IC did not change with age, and this could be because of the function to prevent hip impingement.…”
Section: Discussionmentioning
confidence: 99%
“…The iliocapsularis (IC) originates from the anterior inferior iliac spine and anteromedial part of the hip joint capsule and is inserted into the lesser trochanter (Breckling et al, 2022). The distinctive anatomical features of the IC suggest that its contraction holds significance in stabilising the hip joint through the tightening of the hip joint capsule (Elvan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%